2022
DOI: 10.3390/foods11203241
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Activated Acidic Electrolyzed Water: A New Food Disinfectant for Bacterial Suspension and Biofilm

Abstract: Food-borne diseases are widespread all over the world, and food safety has attracted much attention. This study is the first to use plasma to activate acidic electrolyzed water (AEW) to obtain a new disinfectant for food processing. The germicidal efficacy of plasma-activated acidic electrolyzed water (PA-AEW) on B. subtilis suspension and biofilm was investigated. Furthermore, the synergistic effect of different bactericidal factors was inferred by investigating the physicochemical parameters of PA-AEW and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Plasma-activated acidic electrolyzed water (PA-AEW) was successfully used [134] as a food disinfectant for bacterial suspension and biofilm. The results showed that PA-AEW had a significant bactericidal effect against B. subtilis, a common bacterium used as a model microorganism in research.…”
Section: Atmospheric Pressure Plasma Jets and Plasma Torchmentioning
confidence: 99%
“…Plasma-activated acidic electrolyzed water (PA-AEW) was successfully used [134] as a food disinfectant for bacterial suspension and biofilm. The results showed that PA-AEW had a significant bactericidal effect against B. subtilis, a common bacterium used as a model microorganism in research.…”
Section: Atmospheric Pressure Plasma Jets and Plasma Torchmentioning
confidence: 99%
“…Similarly, Heng et al. (2022) investigated the synergistic application of acidic EW and PAW against bacterial suspension ( E. coli ) biofilms ( Bacillus subtilis ). It was demonstrated that the plasma‐activated acidic electrolyzed water (PA‐AEW) was significantly efficient as a fast disinfectant.…”
Section: Introductionmentioning
confidence: 99%
“…Most review articles related to the application of AWS in FFVs have mostly focused on the specific technology with emphasis on their basic principles, microbial inactivation and safety, and biochemical processes in FFVs (Foudas et al, 2023;Lu et al, 2022;Phan et al, 2021;Rebezov et al, 2022;Soni et al, 2021;Shan et al, 2022;Xiang et al, 2022;Zhang, Wang et al, 2023). Similarly, Heng et al (2022) investigated the synergistic application of acidic EW and PAW against bacterial suspension (E. coli) biofilms (Bacillus subtilis). It was demonstrated that the plasma-activated acidic electrolyzed water (PA-AEW) was significantly efficient as a fast disinfectant.…”
Section: Introductionmentioning
confidence: 99%